Teen pregnancy and educational gaps: Analysis of a national survey in Mexico - Aremis Villalobos-Hernández; Lourdes Campero; Leticia Suárez-López; Erika E Atienzo; Fátima Estrada; Elvia De la Vara-Salazar (Instituto Nacional de Salud Pública, 2015)
Objective. To characterize female adolescents who have been pregnant, and to analyze the association between adolescent pregnancy and educational gaps. Materials and methods. A cross-sectional study was conducted. Data come from the Encuesta Nacional de Salud y Nutrición (Ensanut 2012), a Mexican representative survey. The set of data used is related to sociodemographic and reproductive characteristics from 1 790 women from 12 to 19 years who had begun their sexual life and had a pregnancy record. Three statistical models were adjusted to observe the association between variables. The dependent variable of the first model was the condition of previous pregnancy, the second to be pregnant at the time of data collection, and the third, educational gap. Results. A 74.9% of the adolescents with history of pregnancy has educational gap. To have the condition of previous pregnancy is associated with living with sexual partner (OR=8.4), educational gap (OR=2.4), low socioeconomical level (OR=2.0) and school assistance (OR=0.5). To be pregnant at the time of data collection has related only to living with sexual partner (OR=9.4). The educational gap shows an association with having more than one pregnancy (OR=2.4), live with sexual partner (OR=1.6), low socioeconomical level (OR=1.8), and school assistance as protective factor (OR=0.3). Conclusion. It is necessary to implement effective and efficient educational public politics in order to decrease educational gap. At the same time, to guarantee and improve sexual education in the school system to prevent adolescent pregnancy.